Evaluation of Nutrition Knowledge Levels and Sporting Status of Faculty of Sport Sciences Students - Kocak, Mehmet; Şekeroğlu, Mustafa Önder; Albay, Faruk; Kusan, Osman (Mattioli 1885, 2022)
Study Objectives: Considering that both physical and psychological effects of nutrition and exercise are important on students, this study aimed to evaluate the nutritional knowledge levels and exercise status of the students of the faculty of sports sciences. Methods: 199 students, 146 (73.4%) male, and 53 (26.6%) female, studying at Sivas Cumhuriyet University Faculty of Sport Sciences participated in the study. The scale consists of 20 items on the Basic nutrition and food-health relationship scale, and 12 items on the Food preference scale. One-Way Analysis of Variance (ANOVA) and independent t-test were used because the data showed normal distribution. Pearson Correlation test was used to determine the relationship between the nutritional knowledge levels of the individuals participating in the study and the age and bodyweight groups. Results: There was no significant finding when the total points of basic nutrition and food preference were compared according to the regular exercise status of the participants (p>0.05). A significant finding was found when the total scores of basic nutrition and food preference were compared according to the participants' status of taking nutrition lessons at their schools (p<0.05). Conclusion: In the study, it was revealed that the nutritional knowledge level of the students of the faculty of sports sciences who received nutrition education was sufficient. When the status of doing regular sports is evaluated, it has been revealed that there is no difference between the students who do sports and those who do not, and they have similar nutritional knowledge levels.
Keywords: Nutrition Knowledge Level; Student; Sport Sciences; Exercise; Medical-Students; Consumption